Konsepsi pelajar kursus diploma perakaunan tentang ogif / Sharida Hashim - Sharida, Hashim (2017)
This study aimed to identify the students of Diploma in accounting conceptions of ogive. In particular, this study was undertaken to examine the knowledge of students about the mental image, representation, meaning, construction and interpretation of ogive. Research participants consisted of seven students of Diploma in Accounting selected by purposive sampling aperture variations. The design of study was based on radical constructivism using case studies. Data collected through a clinical interview techniques, while the instrument involved five types of clinical interview protocols. Research participants were interviewed one by one as much as five times in six months. Each interview was audio and video recorded that takes 40 to 60 minutes. In addition, data analysis involved four stages, namely transcription of the interview recording into writing, the establishment of case studies involving descriptions of the behavior of the research participants about aspects of the ogive, analysis and cross- analysis of the participants’ verbal and non-verbal responses, and the identification of the Diploma in accounting students’ conceptions on ogive. The results showed that the students of Diploma in Accounting decipher the meaning of ogive as a form of knowledge that contain specific, useful in daily routine, related to the environment and local culture, but focused on the basic facts and shape in mathematics. In addition, many of the Diploma in accounting students’ conception of ogive describe interconnections with peers in managing the daily routine, while in the process of forming the ogive knowledge also relies heavily on textbooks, teaching and involve logical reason or rational thought. In summary, radical constructivism was used in interpreting the students of Diploma in accounting conceptions of ogive. However, their understanding of the concept of the ogive, the process of knowledge creation and modification on ogive and the correct use of the idea were mostly focused on the level of external surface of understanding against that internal one.